Money Politics in a Contemporary Fiqh Siyasah Review - Sofiyana Nasution; Maulina Roma Yanti Nainggolan; Uliya Putri Yati (Haqqiyyah: Journal of Islamic and Legal Studies, 2025)
This research aims to examine money politics as a form of abuse of power during elections in Indonesia. It analyzes the phenomenon through the perspective of fiqh siyasah, employs a qualitative literature-based method, and proposes normative Islamic solutions, that frequently occurs during elections in Indonesia, and to explore how this practice is viewed in Fiqh Siyasah (Islamic political jurisprudence), which regards money politics as risywah (bribery), a practice prohibited due to its contradiction with the values of justice, trustworthiness, and public welfare. This study employs a qualitative method using a literature review approach. Data were obtained through the exploration and analysis of classical Islamic literature, such as Fiqh books, as well as contemporary references that discuss similar topics. The analytical technique used is descriptive-analytical in order to explore and understand the Islamic perspective on money politics through the lens of Fiqh Siyasah. The findings indicate that money politics not only undermines the integrity of democracy but also fosters corruption, worsens the quality of leadership, and er and erodes public trust in the government system. As a solution, Fiqh Siyasah offers both preventive and curative measures, such as the promotion of Islamic political ethics education, strict law enforcement, involvement of religious scholars in political oversight, and the optimization of Zakat and Infak as legitimate and transparent sources of political financing